A statistical peek into average case complexity. (1st January 2014) - Singh, Niraj K.; Chakraborty, Soubhik; Mallick, Dheeresh K.
The present paper gives a statistical adventure towards exploring the average case complexity behaviour of computer algorithms. Rather than following the traditional count-based analytical approach, we instead talk in terms of the weight-based analysis that permits mixing of distinct operations into a conceptual bound called the statistical bound and its empirical estimate, the so called 'empirical O'. Based on careful analysis of the results obtained, we have introduced two new conjectures in the domain of algorithmic analysis. The analytical way of average case analysis falls flat when it comes to a data model for which the expectation does not exist (e.g., Cauchy distribution for continuous input data and certain discrete distribution inputs as those studied in the paper). The empirical side of our approach, with a thrust in computer experiments and applied statistics in its paradigm, lends a helping hand by complimenting and supplementing its theoretical counterpart.